ANALISIS INVENTORY TURN OVER DALAM MENINGKATKAN PROFITABILITAS PADA MATAHARI DEPARTMENT STORE TBK - Refi Sandria Oktapiadi; Kokom Komariah; Dicky Jhoansyah (Jurnal Ekonomi dan Bisnis, 2019)
Inventory turnover is an important thing that must be considered for each company, how muchinventory is rotating in one period. Because the more frequent inventory turnover, the moreprofit will be generated. The purpose of this study is to find out the Inventory Turn over analysisin increasing profitability at Matahari Department Store Tbk (LPPF) which is listed on theIndonesia Stock Exchange (IDX) for the period 2013 to 2017. This data uses secondary dataobtained from www.idx.co .id. The results of this study have fluctuations in sales from 2013 to2017. Which shows that inventory turnover at Matahari Department Store Tbk (LPPF) is lessoptimal and unstable so that it influences the ability of profits generated by the company.Keywords: Inventory Turn Over, Profitability